2021
DOI: 10.5860/crl.82.3.389
|View full text |Cite
|
Sign up to set email alerts
|

Library Teaching Anxiety: Understanding and Supporting a Persistent Issue in Librarianship

Abstract: Teaching roles in academic libraries can be accompanied by a great deal of anxiety. This study surveyed librarian attitudes toward their teaching role and librarians' experiences with teaching anxiety. Sixty-four percent of librarians participating in the survey said they experienced teaching anxiety, including 65.10 percent experiencing physical symptoms and 73.43 percent of librarians who experienced teaching anxiety experiencing psychological symptoms. Findings indicate tension between sustaining a work-lif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…57 In one recent study, for example, Kacy Lundstrom, Britt Fagerheim, and Stephen Van Geem found that 64.9 percent of 925 librarians indicated that they experienced teaching anxiety and that those who had no coursework in instruction or information literacy were more likely to experience anxiety. 58 If librarians are not getting preparation in instruction or pedagogy, and may experience anxiety or imposter syndrome related to their role in teaching students, it seems likely that teaching the faculty would represent an even bigger hurdle. Bowles-Terry and Donovan point out that, even when librarians may feel confident in their ability to teach undergraduates, there is no guarantee that this confidence would transfer into activities such as instructional consultation or assignment design.…”
Section: Ambivalence Lack Of Preparation Imposter Syndrome and Deferencementioning
confidence: 99%
“…57 In one recent study, for example, Kacy Lundstrom, Britt Fagerheim, and Stephen Van Geem found that 64.9 percent of 925 librarians indicated that they experienced teaching anxiety and that those who had no coursework in instruction or information literacy were more likely to experience anxiety. 58 If librarians are not getting preparation in instruction or pedagogy, and may experience anxiety or imposter syndrome related to their role in teaching students, it seems likely that teaching the faculty would represent an even bigger hurdle. Bowles-Terry and Donovan point out that, even when librarians may feel confident in their ability to teach undergraduates, there is no guarantee that this confidence would transfer into activities such as instructional consultation or assignment design.…”
Section: Ambivalence Lack Of Preparation Imposter Syndrome and Deferencementioning
confidence: 99%
“…Both faculty development and librarianship in general, and library instruction specifically, have been described as involving "emotional labour" (Julien and Genuis, 2009;Matteson and Miller, 2012;Pagowsky, 2021). There are indications that librarians, like developers, may experience impostor syndrome and feel concerned about their abilities (Lundstrom et al, 2021;Martinez and Forrey, 2019). Both groups have also shared concerns about their status in relation to faculty, with librarians, for example, expressing feelings of being disrespected or exploited by faculty (Badke, 2005;Julien and Pecoskie, 2009).…”
Section: Connections Between Developers and Librariansmentioning
confidence: 99%
“…The toll of emotional labour in librarians' teaching roles was further discussed by Julien and Genuis (2009), and the influence of campus structures and power relations on instructional librarians' experiences of the teaching role have been documented (Julien & Pecoskie, 2009). Lundstrom et al (2021) report that most librarians who responded to a survey about anxiety in the teaching role indicated that they experience both physical and psychological symptoms of anxiety. This anxiety was not significantly alleviated by teaching experience but was ameliorated by preparation for the teaching role.…”
Section: Introductionmentioning
confidence: 99%